Covalent organic frameworks: Advances in synthesis and applications. (September 2021) - Altaf, Amna; Baig, Nadeem; Sohail, Manzar; Sher, Muhammad; Ul-Hamid, Anwar; Altaf, Muhammad
Abstract: Covalent organic frameworks (COFs) have emerged as a new class of porous materials. In COFs, the basic rigid molecular building blocks are linked through strong covalent bonds to produce two-dimensional and three-dimensional porous frameworks. COFs are an exciting class of nano-porous materials due to their structural diversity, exceptionally high porosity, and desired tailored chemical structural features. Due to the distinct characteristics of the COFs, they are currently being explored in a wide range of applications such as water decontamination, energy, gas storage, separation, adsorption, and sensing. This review discussed significant advances in the reticular synthesis of COFs and applications in various fields. Finally, the article concludes by discussing the key challenges and future directions of the COFs based materials. Graphical Abstract: ga1 Highlights: Covalent organic frameworks (COFs) are advanced porous materials with exciting applications. COFs are synthesized by reticular stitching of molecular building blocks through strong covalent bonds. Rationally designed COFs can be employed improve the performance of existing devices. The backbone of COFs is comprised of only light elements such as C, O, N and B. COFs are employed in various fields including energy storage devices, catalysis and sensors.